Beneficial effects of kebar grass (Biophytum petersianum klotzsch) ethanol extract to increase motor reflex and spatial memory in mice offspring (Mus musculus) from lactating mothers exposed to carbofuran - Epy Muhammad Luqman; Eka Pramyrtha Hestianah; Widjiati Widjiati; Suryo Kuncorojakti; Viski Fitri Hendrawan (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: This study aimed to determine the potency of kebar grass ethanol extract to overcome an increase in cerebellar neuronal cell necrosis, which has an impact on decreasing motor reflex function and spatial memory of mice from lactating mothers exposed to carbofuran. Experimental approach: Forty lactating mice were divided into four groups, 10 each; including control, T1 (carbofuran 0.0125 mg/day), T2 (vitamin C 5 mg + carbofuran 0.0125 mg/day), T3 (kebar grass extract 3.375 mg + carbofuran 0.0125 mg/day). The mice were orally administered with carbofuran, vitamin C, and kebar grass extract on days 0 to 14 postnatal. On the 15th day, brains of the mice were necropsied to measure the levels of malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione (GSH), H&E staining; motor reflex tests were performed on 10-day-old mice, and the mice aged 30 days were tested on their swimming and spatial memory. Findings / Results: Carbofuran caused an increase in MDA, GSH, neuronal cell necrosis, surface righting reflex, a decrease in SOD, swimming ability, and spatial memory. Kebar grass extract and vitamin C administration decreased MDA, GSH, neuron necrosis, surface righting reflex, and increased SOD, swimming ability, and spatial memory. Conclusion and implications: Exposing to carbofuran in lactating mice caused brain oxidative stress, impaired motor reflexes, and spatial memory in mice offspring. Kebar grass extract and vitamin C administration prevented brain oxidative stress and inhibited disorders in motor reflexes, and spatial memory in mice offspring. Kebar grass extract administration was more effective than vitamin C.